An Exploration of Usefulness of Instructional Learning Methods in Career Selection of Veterinary Graduates - Channappagouda, B; Sharma, G. R. K (Indian Journal of Extension Education, 2016)
The veterinary education in India is facing a paradigm shift which calls for greater emphasis on competency and skill based education. Veterinary Council of India (VCI) is working to address the issues by involving the various stakeholders. However still more in-depth appraisal of students’ perceptions on various aspects of curriculum has not been performed empirically. In this background an attempt has been made to know the graduates overall perception about the different innovative instructional learning methods under VCI-2008 curriculum and their usefulness in career selection. For this purpose, 150 post graduate students were randomly selected from five postgraduate teaching campuses of five south Indian veterinary universities to obtain the information through pre-structured schedule. The study revealed that study circle and tracking courses were found not useful (48.0 per cent and 52.7 per cent respectively) while internship and entrepreneurial training activities were perceived as most useful (71.3 %) and useful (36.7 %) respectively. Further, more than half perceived that clinical (diagnostic) exposure and extension activities as most useful (50.7 % and 61.3 %). The results indicate that much needed emphasis on practical problem solving skills with multidisciplinary approach in the undergraduate curriculum for effective career decisions by graduates.